649 EFFECTS OF THE PREPARATION METHOD ON THE ICG FLUORESCENCE BLOOD FLOW IN THE GASTRIC CONDUIT AFTER ESOPHAGECTOMY. (17th September 2021) - Koyanagi, Kazuo; Ozawa, Soji; Ninomiya, Yamato; Yatabe, Kentaro; Higuchi, Tadashi; Yamamoto, Miho; Tajima, Kohei
Abstract: : In this study, we investigated how the blood flow of gastric conduit changed due to the difference in the lesser curvature cut line using ICG fluorescence imaging in patients with esophageal cancer. Methods: A total of 193 cases of esophageal cancer surgery with gastric conduit reconstruction were included. (Conventional method) The lesser curvature cut line of the stomach was started from a distance of 5 cm from the pylorus (141 cases). (Current method) Gastric lesser curvature dissection was started from the last branch of the left gastric artery (52 cases). Blood flow of the gastric conduit was measured by the ICG fluorescence imaging, and the correlation between the changes in the gastric conduit and both blood flow and anastomotic failure was examined. Results: Median length of the lesser curvature cut line was 10 cm from the pylorus in the current method, which was significantly longer than that in the conventional method (P < 0.001). Congestion at the tip of the gastric conduit were more observed in the conventional method (P = 0.02). The ICG fluorescent blood flow speed in the gastric conduit wall was 2.54 cm/s by the conventional method and 2.82 cm/s by the current method (P = 0.03). There were 23 cases (16.3%) of anastomotic leakage in the conventional method and 4 cases (7.7%) in the current method (P = 0.09). Conclusion: By preserving the right gastric artery and vein, improvement of venous return is expected, and it is suggested that blood flow in the gastric conduit wall can be well maintained.